KAJIAN PUSTAKA : INTERAKSI EDUKATIF DALAM KEGIATAN BELAJAR MENGAJAR - Gloria Walewangko; Elni J Usoh; Jeffry Sonny J Lengkong (Jurnal Genta Mulia, 2024)
This research aims to find information through previous research and other literature reviews regarding aspects of educational interaction in classroom learning. The research method used is literature review. Based on the research results, it was found that there were two aspects of educational interaction in teaching and learning activities. The first is teacher-student communication and the second is student-student interaction. Through these two aspects of educational interaction, it has an impact on student learning motivation which also influences student academic achievement.